Adductor/abductor dysfunction causing patellofemoral syndrome in cyclists - Douglas Reitz, R. (Journal of Science and Cycling, 2024)
Patellofemoral Pain Syndrome is the most common lower extremity musculoskeletal complaint reported by cyclists. Despite the prevalence of research, its pathogenesis and the pathophysiology responsible for this repetitive stress injury has yet to be identified. The most accepted and therefore researched theory involves patellar maltracking arising from the muscular imbalance of the vastus lateralis and vastus medialis. To date, research findings have been inconclusive and many times contradictory. Physical rehabilitation based on those findings has had mixed outcomes, both short and long term. There is a growing body of evidence linking patellofemoral pain syndrome and dysfunction of the hip musculature. This clinical commentary is to elucidate evidence correlating patellofemoral pain syndrome to the muscular dysfunction involving the femoral adductors and abductors in cyclists, thereby directly influencing the alignment and kinematics of the femur.